A Descriptive Study On American Non-Verbal ExpressionsUsed In Jim Carrey's Movies - Rahmawati, Zidni Ika (2005)
The study is about American non-verbal expressions, especially kinesics in Jim Carrey's movies. The objective of the study is to analyze the message conveyed through the use of american non-verbal expressions in jim Carrey's movies. The approach to his study is culture. Thus, in studying non-verbal expressions, people need to understand how one culture determine the message of certain non-verbal expression. The method of conducting the research there are five parts of this chapter, object of the study is American non-verbal expressions used in Jim Carrey's movies, the data are in the form of kinesics behavior. Source of data, are the kinesics used in jim Carrey's movies, technique of data collection are wacthing the movie several time and determining which interaction that use kinesics behavior as the channel of communication. Technique of data analysis are categorizing the kinesics, describing the movement, describing the form and the message are conveyed through the use of kinesics behavior. There are five important points that this study result. The forms of emblems putting index finger to other's lips (used to tell her to be quiet and not to argue him any more) waving hand (used to say good bye). Showing badge of identity (to showed that his badge as a limousine driver). Tossing on palm (someone have done dealing with their dispute) pointing at someone (knowing the joke went success, someone laugh very hard, while pointing at other's) Toss with glass (someone made a toss with glasses, is used to salute someone, as the matchmaker) shrugging one's shoulder (the gesture indicates that he didn't know. What to do about that, as it happened because of his own fault) giving a sign of military honorary (it is usually done by military not just to give an honorary sign its also to congratulate at him) raising punch on air (it is a sign to show that police department were glad someone had got married) waving hand (someone wave his hand with palm down to make a sign that he would not be offended by his explanation). A blink on the eye (this means that the eye contact is used to force other to co-operate with one). Raising eye brow (someone only raised his eye brows and smile. Is a kind of a greeting to the kid. It can compare to verbal channel, Hi") the brrrp on the lips (the movement here indicates that someone didn't want to talk about that). Lowering lips (this means that someone didn't know anything about that, in the sense that he didn't regret his not understanding on that, instead he wanted other's to acknowledge his inability smiling (is used the police not to fine him while to give his driving license). Lowering lips (is used to someone even slapped at other's mouth when he said something impolite at her. So he said "Ok, well go slow" while lowering lip) nodding head (is used to someone to say yes to the question). The forms of illustrators are the thumb up gesture (someone said "good thinking" while showing his thumb up movement, to show one's though that something is good) pointing a direction with thumb (the shopping bag was behind him, so he pointed his back with her thumb, is used to point where the bag was). Hand shaking (is used, to convince the policeman that, they were driving to fast out they didn't drink while saying "oh, no") shrugging one's shoulder (is used to express his not knowing why). Clapping hand (accompanying the verbal channel is used to tell him to come) pointing with index finger to other's (us used he someone warned a kid not to play in the parking lot, because danger, the gesture is used to affirm his warning). Raising one's palm (is used to ask them to wait for her explanation while said, "wait, he's a schyzo). Both palm up gesture (someone had double personalities, they thought each other he appear through that some body, at the same time, one of them stood in front of the mirror and challenged him to come out, he used both palm up to order him to come out). Raising both hand (is used to accompany "calm down") head nodding (someone nodded his head while saying "yeah you wanted to go to aspen he find that girl, is used to confirm his being convinced about that). Moving one's head (is used to someone told to other's to get the bag contained money and move his head toward the seat, is used to direct him where to sit, as in someone pointing which direction to take) nodding head (someone replied a gratitude on him while nodding her head is used to supports her sincere gratitude on him whistling (someone said, "wow, she's an angel". While whistling is used to support his amazement at her. Smiling (someone said, "Guys, he's just a mom, "while smiling, he wanted to add the sense of politeness on his warning) staring at one's eyes (someone stared her eyes and said, "for God sake, give me the number 1", is used to give more force on his being insist to have the number), gazing (when the word I love you come out while gazed each other, is used to supports the verbal channel) the forms affect display are: pulling one's collar (someone said, what was that supposed to mean? "While pulling his collar, is used show anger), pointing with index finger (someone pointed each other right in front of his face with index finger an said, I don't want to hear any word in this house", the warning became strongest accompanied by the gesture) placing both hands on the hips (while saying "Hit and run?", someone placed both of her hands on her hips, is used to express one's anger). A slap on the mouth (someone talked something very rude to other, thus she slapped his mouth, is used to show her anger at someone staring at one's eyes (someone stared at other and asked, Did you forget to pay the gas bill?", is used to express his Anger at someone forgetting to pay the bill) smiling (someone said, she could help him, is used to express she gladness that he was on her trap) crying (someone cried when having to admit that he was sad left by his wife, is a reaction of the sadness) the forms of regulators are: putting index finger on other's mouth (is used to stop other talking) both hand waving (someone waved both of his hands, and other continued his talking, is used to order other to continue talking) nodding head (all the time someone gave the explanation, other pretended to carefully listen to him, is used to order someone to carry on talking while he was listening at him) gazing at one's eyes (someone interesting about something, she said, "Really?" while gazing at him). Smiling (nodding) head and kept on smiling all the time, someone listened to other's explanation, is used to encourage him to continue talking, as it can be interpreted. That a smile is sign of paying attention to someone). The forms of Adaptor: placing hand on chest (someone placed his hand on his chest, while saying, "you remember my name?") squeezing both palm (someone frightening manifested by the gesture he used, that is squeezing his palms) knocking the tip of finger (someone was nervous waiting for the police to interrogate her) placing hand on chest (is reaction of someone being sorry for what her husband has done to him). Placing hands on the forehead (both of them are the forms of reaction of different psychological condition). Scrubbing nose with index finger (someone was either feeling guilty, confused and embarrassed for having done such stupid thing, is used to show the psychological state of him) laughing (knowing the joke went success they laugh very hard, is used as a reaction to something they thought funny) mouth open shaping O (as a reaction of her being shocked). Biting lip (someone bite her lower lip knowing the truth, it can be described that she showed the facial expression because she was having a crush on him) learning one's head backward (someone getting sick of them, he leaned his head backward on the seat) head shaking (feeling afraid that what she thought might be true, she shook her head (staring at one's eyes (someone couldn't believe that other got a he art to do that, he expressed his being shocked). Raising eye brow (someone asked by raised his eye brow is used that someone not sure to other) avoiding the look of others (to showed her being frightened).